PERBANDINGAN TEKNIK KOREKSI BENTUK WAJAH PERSEGI PADA RIAS WAJAH MALAM HARI - Dhiyaa julita Hadiyani (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
We compare two correction techniques namely deep shading and outer shading with only inner shading square face shape at night makeup. This research method uses quasi-experimental methods.The population in this study were women who had a square face shape with 3 people of samples. The results of the analysis show that there is no difference in the level of smoothness in the technique of using shading in the technique of using deep shading and outside shading (p=0,225). But the highest average value was found in the technique of using inner shading and outer shading (X2), which was equal to 3.33. There is a significant difference in the level of sharpness in the technique of using shading in the technique of using deep shading and outside shading (p=0,038). with the highest average value in the technique of using inner shading and outer shading (X2) which is equal to 3.07. There is a significant difference in the level of accuracy in the technique of using shading in with the technique of using shading inside and outside shading (p = 0.038) with the highest average value in the technique of using inner shading and outer shading (X2) which is equal to 3.27.